Langerhans cell congenital histiocytoma. - Manzionna, M.; Aquilino, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
A neonatologist sent us an e mail with a photo of a newborn baby girl presenting on the left shoulder a 7 millimeters in size nodule covered by a blood crust. Hypothesizing a congenital tumor, the nodule was removed under local anesthesia on the third day. On histological examination, there was edema in the superficial dermis and a marked infiltrate consisting of eosinophils and histiocytes with vesicular, eccentric, indented nucleus and abundant cytoplasm with clear-cut borders. These findings were suggestive of Langerhans cells. On immunohistochemical staining, the cells were S-100+ and CD1a+, confirming the diagnosis of congenital Langerhansoma.